The use of toxic agrochemicals in El Huaje, Zentla, Veracruz, México, and their role during the Zafra (harvest) and attempts to control the mosquito Stegomyia aegypti - Marco Antonio Cardoso Gómez; Eunice Victoria García Piña; Mario Uriel Morales Vázquez; Carlos Serrano Sánchez (Social Medicine Publication Group, 2020)
In this paper we describe the population of El Huaje, Veracruz México. This population is composed of Italo-Mexicans, living in El Huaje, Veracruz México. They are employed in the yearly Zafra (sugar cane harvest) and in mosquito measures aimed at reducing the effects of the mosquito Stegomyia aegypti. Structure: This study is qualitative and multi-disciplinary. Objectives: The goal of this study was to describe the processes of cultivating sugar and the efforts made to control the Stegomyia aegypti, mosquito using agro-chemicals. In the course of this study the investigators educated the local population on the use of agro-chemicals. Period of study: January 2016 to December 2017. Data sources: (primary) Information was collected through in-depth interviews, in situ observation, audio and video recordings, notes made "on site as well as" "pictures and a questionnaire." Conclusion: The population of El Huaje is exposed to chronic agro-toxicity caused by the use of agro-chemicals. These chemicals are used in the sugar cane harvest as well as in the control the mosquito: Stegomyia aegypti.